Sex‐related differences in the postmolt distribution of Weddell seals (Leptonychotes weddellii) in the southern Weddell Sea. Issue 2 (5th December 2017) - Langley, Izzy; Fedak, Mike; Nicholls, Keith; Boehme, Lars
Abstract: The population of Weddell seals ( Leptonychotes weddellii ) in the southern Weddell Sea is in a unique position on the continental shelf edge, with vast shelf waters to the south, and deep Southern Ocean to the north. We describe sex‐related differences in the winter distribution of this population, from data collected by 20 conductivity‐temperature‐depth satellite relay data loggers deployed in February 2011 at the end of the annual molt. The regional daily speed was calculated, and a state‐space model was used to estimate behavioral states to positions along individuals' tracks. GLMMs estimated that males and smaller individuals, diving in shallower water, traveled less far per day of deployment (males 14.6 ± 2.26 km/d, females 18.9 ± 2.42 km/d), and males were estimated to dive in shallower water (males 604 ± 382 m, females 1, 875 ± 1, 458 m). Males and smaller individuals were also estimated to be more resident; males spent an average 83.4% ± 7.7% of their time in a resident behavioral state, compared to females at 74.1% ± 7.1%. This evidence that male and female Weddell seals in the southern Weddell Sea are adopting different strategies has not been shown elsewhere along their circumpolar distribution.